THE DISTINCTIVE NATURE OF RIDDLES AND THEIR CLASSIFICATION: A COGNITIVE AND STRUCTURAL ANALYSIS (Eureka Journal of Education & Learning Technologies, 2026)
This study differentiates riddles from other folk genres, such as proverbs and folktales, by analyzing their unique cognitive and structural characteristics. Through an examination of key theoretical frameworks, the paper identifies the riddle’s reliance on semantic ambiguity, inferential reasoning, and the subversion of cognitive scripts as its defining features. The paper further presents a classification system for riddles based on their linguistic mechanisms, thematic content, and the cognitive challenges they present, attributing the theoretical underpinnings to various established scholars. It concludes that the riddle’s distinctiveness lies in its compact, paradoxical formulation designed to activate associative thinking and intellectual surprise, serving as a vital genre for understanding human cognition and cultural transmission.
Keywords: This study differentiates riddles from other folk genres, such as proverbs and folktales, by analyzing their unique cognitive and structural characteristics. Through an examination of key theoretical frameworks, the paper identifies the riddle’s reliance on semantic ambiguity, inferential reasoning, and the subversion of cognitive scripts as its defining features. The paper further presents a classification system for riddles based on their linguistic mechanisms, thematic content, and the cognitive challenges they present, attributing the theoretical underpinnings to various established scholars. It concludes that the riddle’s distinctiveness lies in its compact, paradoxical formulation designed to activate associative thinking and intellectual surprise, serving as a vital genre for understanding human cognition and cultural transmission.